A Novel Spectrum Handoff Method Based On Spectrum Reservation - Peng Yi; Zheng Yong (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this paper, we apply fuzzy analytic hierarchy process (FAHP) method in the decision process of Cognitive Radio Networks (CRN) spectrum handoff. Based on the pre-determined target spectrum list model, considering the multiple indicators which influence the handoff performance, we designed a spectrum handoff method based on spectrum reservation strategy. Simulation results show that the algorithm proposed in this paper exceeds the random handoff algorithm without channel order, it can significantly reduce the handoff frequency and time overhead of cognitive users, reduce the system delay and improve the system throughput. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3573